Otimização da extração de taninos da casca do cajueiro - Sousa, Adriana Dutra (2013)
Tannins are secondary plant metabolites with polyphenolic structure. These compounds have been used in leather tanning, also as replacement for phenol in adhesives manufacture for wood and medical applications. The main sources of these compounds are tree barks, and according to some studies, the stem cashew has great potential to be a source of tannins. In this context, the aim of this study was to optimize the tannins extraction from the cashew bark. Initially, experiments were performed to evaluate the effect of different solvents on the condensed tannins (CT) and total polyphenols (TP) extraction. Dynamic maceration was the technique used for extraction. An experimental design was conducted to understand the influence of some critical variables (time, temperature and liquid/solid ratio) on aqueous extraction of TP and CT, as well as the effect on total solids content (TSC). We tested the effect of bark and solvent reuse in the CT extraction and finally it was evaluated the effect of extracts freeze drying and spray drying. According to results, the extracts obtained with 50% ethanol in water showed higher amounts of TP and CT when compared to other solvents. The variable liquid/solid ratio, the most important factor for all responses, showed positive effect for TP and CT and negative effect on total solids. There is a directly proportional relationship between temperature and levels of TP and CT. Time factor was significant only for CT, where it was observed that 100 minutes favored the extraction. Evaluating the variables relationship, the best condition found for higher levels of tannins was: temperature of 100°C for 100 minutes and liquid/solid ratio 30:1. In this condition, the amount of CT extracted was 7.63 mg catechin equivalent / 100 mg bark. In extraction process, solvent used twice is feasible to extract CT. Unlike the bark, that obtained minimal gains in a second extraction. Spray drying was more suitable for industrial application compared to freeze drying.